A Prospective Comparative Study of Parathyroid Dual-Phase Scintigraphy, Dual-Isotope Subtraction Scintigraphy, 4D-CT, and Ultrasonography in Primary Hyperparathyroidism. (February 2016) - Krakauer, Martin; Wieslander, Bente; Myschetzky, Peter S.; Lundstrøm, Anke; Bacher, Theis; Sørensen, Christian H.; Trolle, Waldemar; Nygaard, Birte; Bennedbæk, Finn N.
Abstract : Purpose: Preoperative localization of the diseased parathyroid gland(s) in primary hyperparathyroidism allows for minimally invasive surgery. This study was designed to establish the optimal first-line preoperative imaging modality. Patients and Methods: Ninety-one patients were studied consecutively in a prospective head-to-head comparison of dual isotope ( 99m Tc-MIBI vs 123 I) subtraction parathyroid scintigraphy (PS), dual-phase PS, 4-dimensional (4D) CT, and ultrasonography (US). Surgery, histological confirmation, and postoperative normalization of Ca ++ and parathyroid hormone were the reference standard. Results: Ninety-seven hyperfunctioning parathyroid glands (HPGs) were identified by the reference standard. Sensitivity and specificity for subtraction PS, dual-phase PS, 4D-CT, and US were 93%, 65%, 58%, and 57% as well as 99%, 99.6%, 86%, and 95%, respectively. Interrater agreement was excellent for subtraction PS (κ = 0.96) while only fair for 4D-CT (κ = 0.34). Pinhole imaging and subtraction of delayed images (the latter especially in case of a nodular thyroid gland) increased the sensitivity of subtraction PS. SPECT/low-dose CT did not increase sensitivity but aided in the exact localization of the HPGs. Of 7 negative subtraction PS studies, 4D-CT and US were able to locate 3 and 1 additional HPGs, respectively. Conclusions: Dual isotope pinhole subtraction PS has higher diagnostic accuracy compared with dual-phase PS, 4D-CT, and US as a first-line imaging study in primary hyperparathyroidism. In case of a negative scintigraphy or suspicion of multiglandular disease, 4D-CT and/or US is recommended as a second-line modality. However, diagnostic algorithms should be adapted in accordance with local availability and expertise.